MENGAPA UKM GARMEN DI KABUPATEN KLATEN MAMPU BERTAHAN DI TENGAH PERSAINGAN PASAR BEBAS? - Tulus Haryono; Siti Khoiriyah; Rum Handayani; Rara Sugiarti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2017)
This study aims to investigate the determinants of Small and Medium Enterprises (SME) can be survive in this free trade era. Using purposive sampling, 100 small medium enterprises are involved as respondent. Descriptive statistic analysis is employed to analyze the research problem. The results indicate that 7P’s have significant effect as a SME’s strategy. The 7P’s strategies represents product, price, place, promotion, people, process, and philosophy. Meanwhile, policy and partner has no significant effect. The results of this study hold important implications for both practitioners and academics. The empirical findings from this study are expected to benefit the continued development of the garment market in Klaten. Possible implications of these results for firms’ marketing strategies and directions for future research are also discussed.